Watou '94 : Beeldende kunstenaars rond de dichter Hugo Claus. - Bloem, Rein; Brems, Hugo; Claes, Paul; Claus, Hugo, 1929-2008; De Coninck, Herman; Mandelinck, Gwij; Piryns, Piet; Wildemeersch, Georges; Exhibition. Watou '94 : Beeldende kunstenaars rond de dichter Hugo Claus. Watou. Wek/Roep Kultuur Watou. 1994 (Watou : Wek/Roep Kultuur Watou, 1994)
Claus, Hugo ; Vanderheyden, JCJ ; Van Severen, Dan ; Dierickx, Karel ; Vanriet, Jan ; Alechinsky, Pierre ; Vandenberg, Philippe ; Wyckaert, Maurice ; Claus, Hugo ; Reinhoud ; Corneille ; Roobjee, Pjeroo ; Lucassen ; Vervisch, Godfried ; Raveel, Roger ; Bogart, Bram ; Claus, Thomas ; Conrad, Patrick ; Vermeersch, José ; Poot, Rik ; Gal ; Tajiri, Shinkichi ; Vandercam, Serge ; D'Haese, Roel
geboortejaar per kunstenaar
zie kast leeszaal
Nederlands
boek